Karakteristik Kejadian Stroke pada Pasien Rawat Inap di RSPAL dr. Ramelan Periode 2020 - Dewi Syahputri (Surabaya Biomedical Journal, 2023)
Stroke is a disease caused by impaired brain function caused by damage or death of brain tissue due to blocked blood flow to the brain so that the oxygen supply is reduced. This disease ranks 3rd after heart cancer in Indonesia. The purpose of this study was to determine the characteristic picture of inpatient stroke patients at RSPAL dr. Ramelan period 2020. The research design uses descriptive research quantitative methods and uses secondary data in the form of medical records. The results of the study totaled 41 samples. The distribution of patients with the most sex factors in the male group was 24 people (59%). The distribution of age factors was highest in the age group of 50-65 years as many as 19 people (46%). The distribution of the family history of the patient is not found in the patient's medical record data. The most diabetes mellitus factor in patients who did not have a history of diabetes mellitus was 23 people (56%). The distribution of patients with the most hypertension factors in the group of patients who had a history of hypertension was 24 people (59%). The distribution of patients with obesity factors was not found in the medical records of patients. The distribution of patients with smoking factors was the most in patients with a history of smoking by 22 people (54%). The conclusion of the study is that the most cases of stroke incidence factors in inpatients at RSPAL dr. Ramelan in 2020 are male, aged 50-65 years, who do not have diabetes mellitus factor, who have hypertension factor, who have a history of smoking, and all samples are declared to have stroke.